A noção de inconsciente em Freud sob a perspectiva do recalcamento - Rodrigues, Helena Zoneti (Universidade Federal de São Carlos, 2022)
The objective of this work is to methodically analyze the notion of the unconscious formulated from the concept of repression (Verdrängung) from the point of view expressed in chapter 7 of the work The Interpretation of Dreams and in Freud's Metapsychological texts, when relating repression as the axis of the formation of the unconscious and to point out the philosophical-theoretical consequences that affect the notion of psychic reality and others such as freedom and determinism. The work seeks to answer the question that intertwines the dual dispositions between the conscious and the unconscious, a dichotomy assured by the concept of repression in the First Topic. In view of the determinations of psychic reality, does the conscious self have freedom in the psychic apparatus of the First Freudian Topic? From the conflicting relationship between the conscious self and psychic reality emerges the main question of the project in which the unconscious emerges in part as a determinant of the dispositions of the conscious self not only in the symptomatic process, in the inhibition of development, in the points of fixation and regression caused by the repression, but as an essential priority, reflected in the phylogenetic schemes and presuppositions in opposition to the ontogenetic process belonging to the conscious self. It is worth investigating which unconscious this is, since its content is not limited only to repressed representations, but also to fragments of the human species, original fantasies. Given these determinations of psychic reality in the apparatus, the instance of the self placed in close relation to consciousness in the First Topic converges to the question posed above and the suspicion that in ontogeny the conscious self is not in fact so predetermined by psychic reality.
Freud's notion of the unconscious from the perspective of repression
Keywords: Eu consciente; Fantasias; Filogênese; Inconsciente; Realidade psíquica; Recalcamento; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA